Anti-quorum sensing evaluation of methyleugenol, the principal bioactive component, from the Melaleuca bracteata leaf oil - Wang, Wenting; Lin, Xiaojie; Yang, Huixiang; Huang, Xiaoqin; Pan, Lei; Wu, Shaohua; Yang, Chao; Zhang, Liaoyuan; Li, Yongyu (Frontiers in Microbiology, 2022)
Quorum sensing (QS) is a cell-to-cell communication in bacteria that couples gene expression through the accumulation of signaling molecules, which finally induce the production of several virulence factors and modulate bacterial behaviors. Plants have evolved an array of quorum sensing inhibitors (QSIs) to inhibit the pathogens, of which aromatic compounds are widely recognized. The essential oil of Melaleuca bracteata was found to exhibit anti-quorum sensing activity, and its principal bioactive component, methyleugenol (ME), had been isolated in our previous study. Here, ME interfered effectively with the QS-regulated processes of toxin secretion in Chomobacterium violaceum ATCC31532, resulting in strong inhibition of QS genes, cviR, cviI, vioA-E, hmsHNR, lasA-B, pilE1-3, and hcnABC, leading to impaired virulence, including violacein production, biofilm biomass, and swarming motility. The accumulation of the signal molecule (N-hexanoyl-DL-homoserine lactone, C6-HSL) in C. violaceum declined upon treatment with ME, suggesting an inhibition effect on the C6-HSL production, and the ME was also capable of degrading the C6-HSL in vitro assay. Molecular docking technique and the consumption change of exogenous C6-HSL in C. violaceum CV026 revealed the anti-QS mechanism of ME consisted of inhibition of C6-HSL production, potentially via interaction with CviR and/or CviI protein. Collectively, the isolated ME, the principal active components of M. bracteata EO, exhibited a wide range of inhibition processes targeting C. violaceum QS system, which supports the potential anti-pathogenic use of M. bracteata EO and ME for treatment of pathogen contamination caused by bacterial pathogens.